A clean approach for the reduction of hazardous 4-nitrophenol using gold nanoparticles decorated multiwalled carbon nanotubes. (1st August 2018) - Al-Kahtani, Abdullah A.; Almuqati, Turki; Alhokbany, Norah; Ahamad, Tansir; Naushad, Mu.; Alshehri, Saad M.
Abstract: 4-Nitrophenol (4-NP) has become anthropogenic pollutant and poses a threat to the environment and human health. The fast detection and reduction of 4-NP can reduced their environmental and health issues. In this study, we have prepared the spherical shaped gold nanoparticles (AuNPs) decorated multi-walled carbon nanotubes (MWCNTs) in the hydrogel matrix. The prepared nanocomposite (Au@MWCNTs) was characterized successfully by several analytical techniques such as FTIR, Ramman, UV–visible spectra, XRD, XPS, and TEM. The surface of MWCNTs was decorated with AuNPs with the diameters range between 10 and 35 nm, the HRTEM results show 2.36 Å interlayer spacing corresponding to (111) crystal planes. The prepared nanocomposite was used as an electrochemical detector in the detection of 4-nitrophenol (4-NP). A large reduction peak was observed at −0.56 V corresponding to the reduction of 4-NP toward p-hydroxyaminophenol using 4 e − processes, additionally two peaks were observed at 0.13 V and 0.19 V corresponding to the redox behavior p-hydroxyaminophenol and p-nitrosophenol. It was clearly observed, that the Au@MWCNts electrode detects at low concentration range with high sensitivity. Moreover, Au@MWCNTs was also used as a catalyst for the reduction 4-NP to 4-AP (4-aminophenol) using NaBH4 via pseudo-first-order and the rate constant was found to be 4.9 × 10 −3  s −1 supporting the promising reduction of 4-NP. Highlights: Gold nanoparticles (AuNPs) decorated multi-walled carbon nanotubes (MWCNTs) were synthesized. Nanocomposite was used for catalytic reduction of 4-nitrophenol. Promising material for 4-nitrophenol electrochemical detection.